RETRACTED: Mammalian STE20-Like Kinase 2 Promotes Lipopolysaccharides-Mediated Cardiomyocyte Inflammation and Apoptosis by Enhancing Mitochondrial Fission - Tian, Yanan; Song, Haijiu; Qin, Wei; Ding, Zhenjiang; Zhang, Ying; Shan, Weichao; Jin, Dapeng (Frontiers in Physiology, 2020)
In this study, we analyzed the role of Mammalian STE20-like protein kinase 2 (Mst2), a serine-threonine protein kinase in LPS-mediated inflammation and apoptosis in the H9C2 cardiomyocytes. Mst2 mRNA and protein levels were significantly upregulated in the LPS-treated H9C2 cardiomyocytes. LPS treatment induced expression of IL-2, IL-8 and MMP9 mRNA and proteins in the H9C2 cardiomyocytes, and this was accompanied by increased caspase-3/9 mediating H9C2 cardiomyocyte apoptosis. LPS treatment also increased mitochondrial ROS and the levels of antioxidant enzymes, GSH, SOD, and GPX in the H9C2 cardiomyocytes. The LPS-treated H9C2 cardiomyocytes showed lower cellular ATP levels and mitochondrial state 3/4 respiration, but increased mitochondrial fragmentation, including upregulation of the mitochondrial fission genes Drp1, Mff and Fis1. LPS-induced inflammation, mitochondrial ROS, mitochondrial fission, and apoptosis were all significantly suppressed by pre-treating the H9C2 cardiomyocytes with the Mst2 inhibitor, XMU-MP1. However, the beneficial effects of Mst2 inhibition by XMU-MP1 were abolished by FCCP, a potent activator of mitochondrial fission. These findings demonstrate that Mst2 mediates LPS-induced cardiomyocyte inflammation and apoptosis by increasing mitochondrial fission.